El Partido de Unión Nacional Saharaui y el fracaso del proyecto neocolonial español - Barona Castañeda, Claudia (El Colegio de México, 2017)
This paper analyzes some of the measures taken by the Spanish government during the period of 1970-1975, when Western Sahara decolonization was prepared. This process sought, above all, the permanence of the metropolis in the area. The first measure was the implementation of the Statute of Autonomy, which aimed to prepare the territory and the population for self-determination. For this purpose, a new political party, representing Spanish policy, was created in 1974: the Sahrawi National Union Party, center of attention in this paper and which reflects the failure of the neocolonial project. A historical perspective is adopted, in spite of the lack of archival materials, due to the Official Secrets Act, valid until today. Personal files and interviews to the people who were part of the changes during those years allows us to think about political and social movements in Western Sahara.